Hubungan Gaya Hidup Dengan Kejadian Penyakit Cholelitiasis Di Ruang Rawat Inap Rsi Surakarta - PURWANTI, ARI, Arina Maliya, A.Kep .,M .S i.Med, Endang Zulaicha S , S.Kp (2016)
Cholelitiasis currently a public health problem because of high frequency and financial burden and social burden to society. Cholelitiasis is the fifth number cause in hospitalization. Based on the many factors that can trigger people's lifestyles cholelitiasis is increasing, like the consumption of fast food with high cholesterol. Cholelitiasis suffered by women at the age of 40 years. The purpose of this study was to determine the relationship between gay life with the incidence of the disease in Ruangh inpatient cholelitiasis RSI Surakarta. This type of research is quantitative. The method used is descriptive analytical case control approach. The subjects of this study were all patients who were hospitalized with a diagnosis cholelitiasis as cases and family of patients as controls, 30 cases 30 respondents respondents control by using total sampling. Data analysis using Chi Square test with significance level (α = 0.05) obtained P value of 0,038 (p <0.05) so that Ho refused and Ha accepted. Concluding that the relationship between lifestyle with an incidence rate of disease in the inpatient unit cholelitiasis RSI Surakarta,odd ratio/OR is 3,000 {95% CI (1,046 < OR < 8, 603)} it meant that respondents with worn out lifestyle had 3,000 times to get cholelitiasis. advice for people, especially people with cholelitiasis to improve healthy lifestyles and avoid fatty foods and high cholesterol.